Effect of force stages approach for sensor less linear DC motor positioning system - Misron, Norhisam (SIRIM, 2007)
Linear motor has gain popularity as linear motion drive in industry and factory automation. These developments were encouraged by the advantages offered by linear motors such as flexibility in size and design, and deliver high performance for applications requiring linear motion. However, the main constraint for system designer to consider linear motors in their application is the cost for every complete package of linear motor. Generally, linear motors are expensive than its counterparts due to the sensory technologies used for positioning system. For typical linear motor driver, a positioning sensor is usually attached to the motor which provide feedback positioning signal to the controller. For some applications, where positioning is not too critical such as robot end gripper, the high precision and expensive positioning sensor is not necessary. Removing this sensor from the system reduce the overall system cost. This research propose a sensor less positioning system for linear DC motor (LDM). The ideas to control the position of the LDM are by controlling the current supplied to the motor by using manipulating technique of Pulse Width Modulation (PWM) signal. A few variant patterns of PWM signal are used to drive the motor which is single stage, dual stage, triple stage and quadruple stage. The variant patterns of PWM signal were created by combining multiple values of duty cycle running in a single PWM signal. A mathematical model for constructed LDM has been derived based on damped force oscillation of mass spring system theory. The equation of motion for LDM is then simulated using Matlab software. The time response of the system based on simulation results has been studied and proper adjustment to control parameters has been made to improve the rise time, overshoot percentage and steady state error.